Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Cv Raflo Dwikarsa Kabupaten Serang - Meldiana Datal; Sam Cay (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - The purpose of this study is to find out the effect of work discipline on employee performance, the effect of the work environment on employee performance, and the effect of work discipline and the work environment together on employee performance. This study uses a quantitative method with 52 respondents who are employees of CV Raflo Dwikarsa. The data used in this study consist of primary data and secondary data. The data were analyzed using descriptive analysis, validity and reliability tests, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, linear regression analysis, correlation analysis, coefficient of determination, t-test, and F-test. The data analysis was carried out using SPSS. The results show that work discipline has a significant effect on employee performance at CV Raflo Dwikarsa, Serang Regency. This is proven by the t value being higher than the t table value (16.384 > 2.009) and a significance value below 0.05. The work environment also has a significant effect on employee performance. This is shown by the t value being higher than the t table value (20.529 > 2.009) and a significance value below 0.05. Work discipline and the work environment together have a significant effect on employee performance. The regression equation is Y = −0.028 + 0.357X1 + 0.640X2. The coefficient of determination is 91.3%, while the remaining 8.7% is influenced by other factors. The F test shows that the calculated F value is higher than the F table value (258.249 > 3.187).